Old and new adventures with fatty acids and their oxylipins: The road towards personalised clinical nutrition - Gibson Robert (EDP Sciences, 2021)
After paying homage to the work of E. Chevreul, Prof. Robert Gibson went on in a lighthearted way to find similarities in the way they both approached their respective fields of research, as well as their way of life. Prof. Robert Gibson, who was awarded the 2021 Chevreul Medal, reported that “his huge delight was to witness the massive growth of lipid research and to have played a role in elucidating the role of dietary fats in the health of mothers and their babies”. Prof. Gibson highlighted some of the major results he collected from Australian clinical studies conducted on the role of omega-3 fatty acids on the health outcomes of mothers and their infants. He first discussed the role of fish oil on visual acuity of babies and demonstrated that infant formulas supplying more than 1% of linolenic acid (ALA) seemed adequate to ensure optimal visual and cognitive development of term infants. However, in preterm infants, whether there is a specific need for DHA above the benefit provided by ALA, still needs to be clarified. He reported a small beneficial impact on the cognitive development of preterm infants receiving DHA enriched breast milk of their mothers (1% of total fatty acids). He then discussed data from his large randomised clinical trials conducted on pregnant women receiving a DHA dietary treatment (800 mg/d DHA) or placebo, that suggested that DHA may decrease the risk of preterm birth (DOMInO trial, 2400 women). This effect was confirmed in the ORIP trial (5400 women) which found that preterm birth could be prevented by a DHA supplement treatment mainly in women with a singleton pregnancy who had a low omega-3 status in the first trimester. In the last part of his review, Robert Gibson described the use of a new low cost, rapid and efficient method to monitor changes in blood levels of omega-3 fatty acids with clinical outcomes: the Dried Blood Spots (DBS) technology. The validation of this technique has been demonstrated in large trials like N3RO and ORIP involving large cohorts of women, which could not have been obtained easily by classical analysis of lipids. He went on to point out that free fatty acids (generally not explored despite their importance in many metabolic disorders) and oxylipins, are both stable and easily identified when they are preserved in a dry state on a paper matrix (DBS), thus opening new fields of research. To conclude, the major impact of Prof. Robert Gibson’s work was identifying and overcoming one of the causes of early preterm birth (omega-3 deficiency), developing a tool to rapidly assess omega-3 status (the DBS technique) that together is close to being implemented into the world health system.